Genetic heterogeneity of actionable genes between primary and metastatic tumor in lung adenocarcinoma. Issue 1 (December 2016) - Kim, Eun; Cho, Eun; Park, Heae; Kim, Arum; Hong, Ji; Lim, Seri; Youn, Jong; Hwang, Seung; Chang, Yoon
Abstract Background Biopsy for lung cancer diagnosis is usually done at a single site. But it is unclear that genetic information at one biopsy site represents that of other lesions and is sufficient for therapeutic decision making. Methods Non-synonymous mutations and insertions/deletions of 16 genes containing actionable mutations, and intron 2 deletion polymorphism ofBcl2-like11 were analyzed in 41 primary tumor and metastatic lymph node (L/N) matched, pStage IIA ~ IIIA non-small cell lung cancer (NSCLC) samples using a next generation sequencing based technique. Results A total of 249 mutations, including 213 non-synonymous mutations, 32 deletions, and four insertions were discovered. There was a higher chance of discovering non-synonymous mutations in the primary tumors than in the metastatic L/N (138 (64.8%)vs. 75 (35.2%)). In the primary tumors, 106 G > A:C > T transitions (76.8%) of 138 non-synonymous mutations were detected, whereas in the metastatic L/N, 44 (58.7%) of 75 were discovered. A total 24 (11.3%) out of 213 non-synonymous mutations were developed in the context of APOBEC signature. Of those, 21 (87.5%) was detected in the primary tumors and 4 (16.7%) was detected in the metastatic L/N. When the mutation profiles between primary tumor and metastatic L/N were compared, 13 (31.7%) of 41 cases showed discrepant mutation profile. There were no statistically significant differences in disease free survival and overall survival between groups showing identical mutation profiles and those with discrepancy between primary and metastatic L/N. Conclusions Genetic heterogeneity between the primary and L/N metastatic lesions is not infrequent finding to consider when interpreting genomic data based on the result of one site inspection. A large prospective study may be needed to evaluate the impact of genetic heterogeneity on the clinical outcomes of NSCLC patients.